FEATURES OF CORTICAL FUNCTIONAL ACTIVITY IN PATIENTS WITH PARKINSON'S DISEASE AFTER DEEP BRAIN STIMULATION IN THE LONG-TERM POSTOPERATIVE PERIOD - Uzakova Gulnoza Farruxovna; Shomurodova Dilnoza Salimovna (Scholar Express Journals, 2025)
The aim of this study is to analyze the features of cortical functional activity in patients with Parkinson's disease (PD) who have undergone deep brain stimulation (DBS) in the long-term postoperative period. A comparative evaluation of electroencephalographic (EEG) data was carried out in two groups of patients — those who had undergone neuromodulation and those receiving only pharmacological treatment without surgical intervention. The study revealed significant differences in bioelectrical brain activity, indicating the long-term effects of DBS on the functional state of the cerebral cortex and a possible tendency toward both compensatory and maladaptive neural reorganizations over time
Keywords: Parkinson's disease; deep brain stimulation; neuromodulation